Who Is Willing to Pay for Online Journalistic Content? - Himma-Kadakas, Marju (2015)
While the overall readership of newspapers is growing as a result of the multiplatform reach, many online media consumers are not offered the surplus value they expect of journalistic content. Since a great deal of journalistic content published on the internet has been free of charge for years, attempting to monetarise this content is now proving complicated. This article considers the motivating factors behind attitudes towards paying for online journalistic content in different population groups. We follow two directions: attitudes towards paying for online news, and obstacles that compromise willingness to pay in different groups. The survey results and trends noticed by media organisations indicate that the public’s readiness to pay for journalistic online content is growing, albeit slowly. Based on the outcomes of various interviews we can conclude that the expectation of exclusive quality and web distinctive content are the two main reasons behind willingness to pay for online journalistic content, however, it is difficult to outline particular preference groups based on cultural, demographic, or socio-economic characteristics. This seems to be the result of audience fragmentation—the reasons behind willingness to pay for online journalistic content are hidden in the interests and preferences of small audience groups.